Spatial and Discursive Violence in the US Southwest - Sánchez, Rosaura; Pita, Beatrice (Book collections on Project MUSE., 2021)
"Analyzing a range of Chicano/a and Native American novels, films, short stories and other cultural artifacts from the eighteenth century to the present, Rosaura Sánchez and Beatrice Pita examine literary representations of settler colonial land enclosure and dispossession in the US Southwest."--